Anomalous systemic and pulmonary veins—An unusual coexistence. Issue 5 (12th April 2018) - Arunakumar, Priyadarshini; Ayyappan, Anoop; Sasikumar, Deepa; Krishnamoorthy, KM
Abstract : A 12‐year‐old child presented with recurrent respiratory infections and was diagnosed with Scimitar syndrome. Drainage of IVC and course of aberrant arterial supply from aorta were not clear by echocardiogram, and hence, additional imaging was planned. CT unraveled the presence of a rare combination of anomalous pulmonary venous connection (APVC) to IVC, with near‐atresia/severe stenosis of IVC, superior to the drainage of scimitar vein. There was a prominent azygos vein with preferential contrast opacification on lower limb injection.